Implementation of Islamic Religious Education in Nurturing Religious Moderation and Mutual Respect in Multicultural School Contexts - Ilmiah, Masniatul; Mashudi; Saihan (Program Studi PGMI, 2025)
This study aims to analyze the role of Islamic Religious Education (IRE) in nurturing religious moderation and mutual respect within the multicultural school environment of SDN 5 Gubug, Tabanan Regency. The research employed a qualitative case study approach. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that Islamic Religious Education plays a strategic role in cultivating religious moderation through contextual learning, the integration of local wisdom such as Tri Hita Karana, and the promotion of interfaith understanding among students. The implementation of IRE is supported by teacher pedagogical competence and inclusive school policies that encourage tolerance and social harmony. However, challenges arise from external influences, including exclusive digital religious content and limited parental involvement. Overall, Islamic Religious Education at SDN 5 Gubug functions as an effective medium for fostering tolerance and mutual respect from an early age. Continuous teacher development and strengthened collaboration between schools, families, and communities are essential to sustain and enhance the impact of religious moderation education at the elementary level.